Sniffing Pada Jaringan WiFi Berbasis Protokol 802.1x Menggunakan Aplikasi Wireshark - Abdillah, Muhamad Aznar; Yudhana, Anton; Fadil, Abdul (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Nowadays WiFi technology is increasing with the people's need for internet access. WiFi is an abbreviation of Wireless Fidelity. WiFi can be said to be a technology for exchanging data by utilizing radio waves (wireless) that can be used by several electronic devices such as computers, smartphones, tablets, and so on. This research tries sniffing method on WiFi-based 802.1X protocol to get the client authentication code. The conclusion obtained from this study is the Sniifing Process using the Wireshark application managed to get the station authentication code on an 802.1X-based WiFi network. The authentication code can be used when the station is no longer connected to a WiFi network. This can be used by other people or stations that are actually not entitled / illegitimate.